Travel with Diabetes: A Comprehensive Review for Clinicians - Venkatraman Rajkumar (Dubai Diabetes and Endocrinology Journal)
Background: Travel has become an integral part of life, whether for business, pleasure, sport, or pilgrimage. The increasing number of patients with diabetes mellitus translates to a greater number of travelers with this condition. Primary care physicians have little knowledge to guide patients with diabetes planning travel. Summary: A structured pre-travel evaluation coupled with patient education diminishes health problems during travel. Proper preparation should include completion of all required immunizations, evaluation of diabetes, its co-morbidities, and their control prior to departure. This article discusses travel on foot, by road, railroad, sea route, and air travel; the supplies needed; and the unique features of each modality. This article discusses blood glucose monitoring, air travel security, precautions with continuous glucose monitors and insulin pumps during ascent and descent of aircraft, insulin dosage adjustments during travel beyond time zones, proper preservation of insulin in extreme temperatures, and adaptation to high altitude, hot and cold environments for patients with diabetes. Key Messages: There is a need for standardized guidelines based on expert opinions and best practices for travelers with diabetes, disposal of sharps, used test strips, and swabs in the absence of prospective studies.